The Impact of Artificial Intelligence (AI) on Human Resources: A Case Study of the Indonesian Police Institution - Widya Septiyandini; Chairul Muriman; Vita Mayastinasari (Transpublika Publisher, 2025)
Artificial Intelligence in the digital era has brought significant changes in the way companies manage and utilise human resources. Artificial Intelligence is expected to assist in various aspects of human resource management, particularly in military or state security sectors. This study focuses on the impact of AI on human resources within the Indonesian police force. The use of AI tools in managing the large amount of employee data in the police force is seen as beneficial. Matching the right person with the right job is a key challenge for human resource professionals, which AI and automation technology can help with. AI aids in forecasting future employee needs and making effective recruitment choices. Performance management tools driven by AI offer opportunities for both employees and organisations in police forces. AI can also help in evaluating employees fairly through multi-attribute decision-making processes. Additionally, AI systems can assist managers in determining appropriate compensation and benefits for police personnel.